Implementation of Minimum Competency Assessment Simulation Test Instruments in Numeracy Literacy Based on Local Culture at Muhammadiyah Elementary School Special Program Baturan - Muhammad Misbahqul Umam; Fitri Puji Rahmawati (FKIP - Universitas Riau, 2026)
The numeracy literacy of elementary school students is still low, as reflected in Indonesia's 72nd ranking in PISA 2018, with difficulties in connecting number concepts and arithmetic operations to real contexts. Therefore, this study aims to analyze the implementation of simulation instruments for the Minimum Competency Assessment (AKM) of numeracy literacy based on the local culture of Karanganyar, such as the enggrang game, getuk cuisine, and Jatigede Reservoir tourism, on 30 fourth-grade students at Muhammadiyah PK Baturan Elementary School during October-November 2025. Using a qualitative descriptive method with a case study approach involving triangulation of sources (teachers-students-researchers) and techniques (in-depth interviews, participatory observation, documentation), data analysis through reduction, presentation, and conclusion drawing showed positive results: 66.7% of students achieved the proficient/competent category (score ≥70 from a previous average of 65), 73.3% were very active and active during the test, and there were positive responses to the cultural context that increased cognitive-affective engagement. In conclusion, this ethnomathematics approach can improve meaningful numeracy literacy, reduce math anxiety, enrich cultural literacy, and is recommended for continuous implementation for elementary school students who need additional guidance and as an enrichment program for gifted students.